Optical MEMS for chemical analysis and biomedicine - Jiang, Hongrui (The Institution of Engineering and Technology, 2016)
Optical MEMS are micro-electromechanical systems merged with micro-optics. They allow sensing or manipulating optical signals on a very small size scale using integrated mechanical, optical, and electrical systems and hold great promise specifically in biomedical applications, among others. This book describes the current state of optical MEMS in chemical and biomedical analysis with topics covered including fabrication and manufacturing technology for optical MEMS; electrothermally-actuated MEMS scanning micromirrors and their applications in endoscopic optical coherence tomography imaging; electrowetting-based microoptics; microcameras; biologically inspired optical surfaces for miniaturized optical systems; tuning nanophotonic cavities with nanoelectromechanical systems; quantum dot nanophotonics - micropatterned excitation, microarray imaging and hyperspectral microscopy; photothermal microfluidics; optical manipulation for biomedical applications; polymer-based optofluidic lenses; and nanostructured aluminum oxide-based optical biosensing and imaging. Bringing together topics representing the most exciting progress made and current trends in the field in recent years, this book is an essential addition to the bookshelves of researchers and advanced students working on developing, manufacturing or applying optical MEMS and other sensors.
Keywords: Optical MEMS.; elektronické knihy; electronic books